Pertanggungjawaban Hukum Atas Pelanggaran Kode Etik Melalui Promosi Oleh Notaris (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
In order to maintain the integrity and dignity of their position, Notaries are required to comply with the Code of Ethics, including the prohibition on job promotions as stated in Article 4 paragraph (3) of the Notary Code of Ethics. However, violations of this rule are still frequently encountered. This study uses a doctrinal method by reviewing primary legal materials, such as the Notary Law, Minister of Law and Human Rights Regulation Number 19 of 2019, and the Notary Code of Ethics, as well as secondary legal materials in the form of books, legal journals, and interviews with the Chairperson of the Regional Board, Former Regional Honorary Council, and Members of the Indonesian Notary Association. The purpose of the study is to determine and analyze the position of the Notary Code of Ethics as a public official regarding violations committed, as well as to examine the form of legal accountability for violations of the code of ethics related to job promotions. The results of the study indicate that although the Notary Code of Ethics is binding, many Notaries still violate it, especially through job promotion practices that are contrary to the principles of professionalism and reduce public trust. Existing forms of accountability are still limited to ethical, moral, and social aspects within the scope of professional organizations, thus not being effective enough to create a deterrent effect, especially for notaries who repeatedly seek promotions. This research also revealed that although the Notary Code of Ethics provides clear provisions regarding the prohibition of promotions.